2022
DOI: 10.3892/mco.2022.2538
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of prognosis using the Gynecology Oncology Group score of stage IB‑IIA node negative uterine cervical cancer after radical hysterectomy and trachelectomy

Abstract: There is currently controversy regarding the criteria for low and intermediate risk of cervical cancer (CC) after surgery. In the present study, the Gynecology Oncology Group (GOG) score was used to detect intermediate risk. Adjuvant radiotherapy was applied in the case of a GOG score >120. The present study aimed to evaluate the validity of the recurrence risk classification using the GOG score for stage IB-IIA node-negative CC. All cases of stage IB-IIA node-negative CC who underwent radical surgery between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, this approach has a risk of tumor spillage, and its use is being phased out in Europe for this reason. Loose closure has been suggested as the cause [ 14 15 ]. Therefore, we used barbed sutures during vaginal cuff creation to ensure the sutures did not loosen.…”
Section: Discussionmentioning
confidence: 99%
“…However, this approach has a risk of tumor spillage, and its use is being phased out in Europe for this reason. Loose closure has been suggested as the cause [ 14 15 ]. Therefore, we used barbed sutures during vaginal cuff creation to ensure the sutures did not loosen.…”
Section: Discussionmentioning
confidence: 99%
“…These factors have been shown to be independent prognostic factors for a 3-year disease free interval in patients with cervical cancer [ 17 ]. This has been used by many institutions, and it has been shown that patients with a GOG score <70 are associated with good recurrence-free survival without adjuvant therapy [ 18 ]. However, patients with a GOG score >120 have a 41% risk of recurrence without adjuvant therapy after radical hysterectomy and the standard of care for patients with a GOG score between 70 and 120 is less clear [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%